Investigation on the Application of Different Air-Cooling-Systems in a Thermoelectric Setup. (2015) - Roj, Robin; Katenbrink, Nils
Abstract: This paper presents the differences as well as the advantages and disadvantages of three different standard air cooling systems in a thermoelectric setup. Beside the investigation of their efficiencies, also the fields of application of all three possibilities have been examined. In order to create significant effectiveness diagrams, a series of measurements has been conducted. For that reason different Peltier elements or thermoelectric coolers (TECs), respectively, made from bismuth telluride based alloyswere used to temper a metallic test specimen consisting of a copper block, that was heated up by an external source with a specified energy. On the hot side state-of-the-art heatsinks were attached, while the cold side was equipped with a copper block as well as an electric heater. Due to measurements at ambient temperature, the heat flow itself was assumed to be perfectly constant, no heat losses had to be taken into account. By temperaturemeasurements on the hot as well as on the cold side of the Peltier elements, the dissipated heat that was conducted by the air cooling systems has been determined. In addition to that, the results are visualized in expressive diagrams that allow the viewer to judge the performance of the cooling systems and Peltier elements at first sight.